Beginning C# 2008 From Novice to Professional - Gross, Christian (Apress : Imprint: Apress, 2008)
This book is for anyone who wants to write good C# code-even if you have never programmed before. Writing good code can be a challenge-there are so many options, especially in a .NET language like C#. If you want to really get the best from a programming language, you need to know which features work best in which situations, and understand their strengths and weaknesses. It is this understanding that makes the difference between coding and coding well. Beginning C# 2008: From Novice to Professional, Second Edition has been written to teach you how to use the C# programming language to solve problems. From the earliest chapters and the first introductory concepts, you'll be looking at real-world programming challenges and learning how C# can be used to overcome them. As you progress through the book, the problems become more involved and interesting, while the solutions become correspondingly more complex and powerful as C# features interact to achieve the results that you want. This second edition has been revised and improved to now include the SQL Server 2008 release and explain how you can integrate SQL Server 2008 with your C# applications. By the time you've finished reading this book and worked through the sample exercises, you'll be a confident and very competent C# programmer. You will still have many explorations of the .NET Framework API to look forward to, but you will have a firm foundation to build from, and you will know exactly where to go to find the things that you need to progress confidently in your projects.